Rebuilding Public Trust Through Ethical Governance and Transparency: A Mixed-Methods Study of Nigerian Federal Ministries and Implications for Health Service Delivery - Yakubu Joel Cherima; Uchenna Stephen Nwokenna; Rejoice Kaka Hassan; Eziyi Iche Kalu; Agwu Nkwa Amadi; Faith Adamma Kalu; Perfection Chinyere Igwe; Justin Junior Kalu; Beauty Olamma Kalu; Ugo Uwadiako Enebeli (European Scientific Journal, ESJ, 2026)
Background: The persistent public distrust in Nigerian federal institutions stems from entrenched corruption, fragmented ethical standards, and non-transparent governance, which erode legitimacy and policy compliance despite reforms like the Freedom of Information (FOI) Act. This study assessed ethics and transparency in federal ministries to propose a framework for enhancing ethical leadership and accountability.Methods: We used a mixed methods design which involved policy/institutional audits and surveys (n=200 civil servants) across five key federal ministries (Finance, Health, Education, Works and Housing, and Humanitarian Affairs) in Abuja, the Federal Capital Territory of Nigeria. Quantitative data on ethical perceptions, corruption prevalence, and transparency effectiveness were analyzed using descriptive and inferential statistics, while qualitative key informant interviews and document reviews enabled thematic analysis.Results: Ethics codes were highly recognized by the participants (mean=4.01/5), but enforcement (3.40), reporting (3.20), and integrity offices (3.08) scored moderately. Corruption was perceived as widespread (4.12/5), with low rewards for ethics (2.80) and reporting efficacy (2.55). Transparency mechanisms (financial disclosure=3.35; public access=3.10; procurement=2.90) were moderate, with political interference (4.5/5) and fragmented coordination (4.3/5) as top challenges; a strong correlation linked ethics infrastructure to public trust (r=0.715, p<0.01).Conclusions: Ethics and transparency in Nigerian ministries remain weakly enforced and undermine public trust, and robust ethical systems correlate strongly with public trust. We propose a Public Integrity and Transparency Framework (PITF) that integrates digital dashboards, leadership audits, ethics curricula, and incentive-linked benchmarking into a practical model that embeds value-driven accountability. The PITF will inform governance reforms for sustainable trust restoration.